Advances in Microbial Biotechnology : Current Trends and Future Prospects - Kumar, PhD., Pradeep; Kumar Patra, Jayanta; Chandra, Pranjal; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
Over the last few decades, the rapid and vast development of advanced microbial bioresources and metagenomics techniques has completely transformed the field of microbial biotechnology. Our understanding of microbial diversity, evolutionary biology, and microbial interaction with their animal and plant hosts at molecular level has been revolutionized with an abundance of new research. This new volume, Advances in Microbial Biotechnology: Current Trends and Future Prospect, focuses on the application of microorganisms for several purposes: for plant protection and improvement, for environmental remediation purposes, and for the improvement of human health. Various applications of microorganisms are covered broadly and have been appropriately reflected in depth in different chapters. The book is divided into four major sections: applied microbiology in agriculture, microbes in the environment, microbes in human health, microbes in nanotechnology The book provides insight into the diverse microorganisms that have been explored and exploited in the development of various applications for agricultural improvements. The book also looks at the application of microbes for the removal of pollutants and the recovery of metals and oils. Also discussed is the detection and exploitation of microorganisms in the diagnosis of human diseases, providing possible holistic approaches to health. This new volume will provide a wealth of information on new research on the application of microbial biotechnology today.
The Genomics of Major Foodborne Pathogens: An Update --Spiros Paramithiotis and Eleftherios H. Drosinos -- Microbial Beta Glucanase in Agriculture -- --Lekshmi K. Edison, S. Shiburaj, and N. S. Pradeep -- Application of Plant Growth Promoting Rhizobacteria in Agriculture -- --Sushanto Gouda, Rout George Kerry, Dibyaranjan Samal, Gyana Prakash Mahapatra, Gitishree Das, and Jayanta Kumar Patra -- Microbial Pesticides: Potential Alternative -- --Bigneswar Baliyarsingh, Aseem Mishra, and Saktikanta Rath -- Microalgae: A Potential Source of Biofuel -- --Devendra Kumar, Priyanka Nehra, Anuj Kumar, and Neeraj Kumar -- Prospects and Application of Azospirillum Spp. as a Natural Agricultural Biofertilizer -- --D. Mohapatra, N. R. Singh, and S. K. Rath -- Yeast: A Multifaceted Eukaryotic Microbe and Its Biotechnological Applications -- --Nayan Moni Deori, Rachayeeta Deb, Riddhi Banerjee, and Shirisha Nagotu -- Antimicrobials for Textile Finishes -- --Sagarika Devi -- Influence of Wastewater Use in Agriculture: Advances in Human and Plant Health -- --Kavindra Kumar Kesari and Vijay Tripathi -- Microbial Fuel Cells for Wastewater Treatment, Bioremediation, and Bioenergy Production -- --Ravinder Kumar and Pradeep Kumar -- Role of Microorganisms in the Removal of Fluoride -- --Shubha Dwivedi, Prasenjit Mondal, and Chandrajit Balomajumder -- Application of Microorganisms in Biodegradation of Cyanide from Waste Water -- --Naveen Dwivedi, Chandrajit Balomajumder, and Prasenjit Mondal -- Microbial Infections and Human Health: What Ayurveda Can Offer -- --Chethala N. Vishnuprasad -- Bacteria Biofilms and Their Impact on Human Health -- --Mukesh Kumar Yadav -- Prevention of Colorectal Cancer Through Probiotics, Prebiotics and Synbiotics: A Critical Review -- --Sushrirekha Das, Smita H. Panda, Niladri B. Kar, Nakulananda Mohanty, and Hrudayanath Thatoi -- Purification and Characterization of Microbial Polygalacturonases: An Update -- --Gautam Anand, Sangeeta Yadav, Aiman Tanveer, and Dinesh Yadav -- Natural Agents Against Filariasis: A Review -- --Vishal Kumar Soni -- Maximizing Expression and Yield of Human Recombinant Proteins from Bacterial Cell Factories for Biomedical Applications -- --Manash P. Borgohain, Gloria Narayan, H. Krishna Kumar, Chandrima Dey, and Rajkumar P. Thummer -- Microbes and Nanotechnology: A Potent Confluence -- --Reecha Sahu and Lata S. B. Upadhyay -- Potential Applications of Nanotechnology: An Interface in Modern Science -- --Anjan Kumar Pradhan and Sushil Kumar Sahu -- A Systematic Study on Phytosynthesized Silver Nanoparticles and Their Antimicrobial Mode of Action -- --Anupriya Baranwal, Ananya Srivastava, and Pranjal Chandra
Includes bibliographical references and index.
Also available in print format.
Keywords: Microbiology; Microbial biotechnology; Microbiological Phenomena; Biotechnology -- trends; Crop Science; Biotechnology; AGRICULTUREnetBASE; BIOSCIENCEnetBASE; SCI-TECHnetBASE.; BIOMEDICALSCIENCEnetBASE; LIFESCIENCEnetBASE; STMnetBASE; SCIENCE / Life Sciences / Biology / Microbiology; TECHNOLOGY & ENGINEERING / Agriculture / General; Electronic books